Digitalization of Production Management and Raw Material Stock for Convection Business: Case Study of Web-Based Manteq Distro & Convection - Putri, Rizqi Laili; Listyorini, Tri; Supriyati, Endang (STMIK Banjarbaru, 2025)
This study raises issues related to management at Manteq Distro & Konveksi, this UMKM business produces plain t-shirts, screen-printed t-shirts, shirts, jackets, school uniforms. In the midst of today's technological advances, Manteq Distro & Konveksi has not used an information system, in recording product data and managing raw materials, writing is still done conventionally, as a result this method is less efficient and requires more time. The study focuses on creating a web-based information system at Manteq Distro & Konveksi to manage raw material stock and production. Using the waterfall method with the stages of needs analysis, design, development, testing, and implementation. To improve operational efficiency, the convection business must implement digitalization in managing production and raw material stock. This system has the latest algorithm to predict raw material needs, real-time stock management, and production data recording. The system is built using Visual Studio Code and the PHP, MYSQL programming languages. The system testing method uses blackbox testing to ensure that each function runs as needed.Keywords: Digitalization; Production management; Raw material stock; Information system; Convection Abstrak Penelitian ini mengangkat permasalahan terkait pengelolaan di Manteq Distro & Konveksi, usaha UMKM ini memproduksi kaos polosan, kaos sablon, kemeja, jaket, seragam sekolah. Di tengah kemajuan teknologi saat ini, Manteq Distro & Konveksi belum menggunakan sistem informasi, dalam melakukan pendataan produk dan pengelolaan bahan baku penulisannya masih dilakukan secara konvensional, akibatnya metode ini kurang efisien dan memerlukan lebih banyak waktu. Penelitian berfokus pada pembuatan sistem informasi berbasis web di Manteq Distro & Konveksi untuk mengelola stok bahan baku dan produksi. Menggunakan metode Waterfall dengan tahapan analisis kebutuhan, perancangan, pengembangan, pengujian, dan implementasi. Untuk meningkatkan efisiensi operasional usaha konveksi harus menerapkan digitalisasi dalam pengelolaan produksi dan stok bahan baku. Sistem ini memiliki algoritma terbaru untuk memprediksi kebutuhan bahan baku, manajemen stok secara real-time, dan pencatatan data produksi. Sistem di bangun menggunakan Visual Studio Code dengan bahasa pemrograman PHP dan MYSQL. Metode pengujian sistem ini menggunakan Blackbox Testing untuk memastikan bahwa setiap fungsi berjalan sesuai yang dibutuhkan.